DEVELOPMENT OF FOOD PRODUCTS FROM MILLET - Aller, Margie C.; Neri, Alfredo C.; Dela Cruz, Adeline P. (Journal of Agriculture and Technology Management, 2012)
The study generally seeks to develop food products utilizing millet grain and millet flour. This millet grain/flour served as the main ingredient in preparing the food products and as a partial substitute to the all- purpose and/or cake flour. Specifically, it aims to utilize millet in baking pastries, cookies, and cakes, and cooking pastillas; to evaluate these food products in terms of consumer acceptability; and to produce a techno–pack on the developed food products for extension service. The experimental method was used in this study to develop products like millet tart, millet (chiffon) cake, millet cookies, and millet pastillas from millet grain and flour. The formulation employed was based on the basic procedure in the preparation and processing for standard recipes. The 9-point Hedonic rating scale was used to evaluate the first and second phase of the product acceptability testing. Millet can be utilized as main or added ingredient in baking pastries, cookies and cakes, and cooking pastillas. Specifically, millet flour can be used as added ingredient in baking cookies and cakes, while millet grain can be utilized as main ingredient in cooking tart fillings and pastillas. Assessment on consumer acceptability reveals that millet tart, millet cake, millet cookies and millet pastillas can be considered as possible processed products that utilized millet. A techno-pack for each of the developed products can be produced for extension services. Among the four recipes formulated, millet pastillas has higher consumer acceptability as “like very much” compared to only “like moderately” for the rest of the millet recipes developed.